Repository conversations - Baptista, Ana Alice (2007)
For a long time the importance of informal communication is admitted (e.g. email, out of question) in the context of creation and share of scientific knowledge. However, there have been few initiatives that try to exploit the advantages of the existence of an informal communication layer that complements the classic mechanisms of formal scientific communication. This article describes the developments that resulted of the DSpace-dev @ University of Minho project, focusing especially on the Commenting add-on: An extension developed for the DSpace platform, which has as an objective to provide Institutional Repositories with informal communication capacities. The article approaches, in addition, some ideas that can be taken as a basis for future developments about this subject matter, namely: To transform the add-on into multi-repository and multiplatform, to manage to each comment to be accompanied by descriptive metainformation in order to facilitate its location by search engines, and to improve significantly its graphical user interface.